L’économie circulaire au Sénégal : appropriation des principes par les pouvoirs publics et mise en relation avec les pratiques endogènes - Ndèye Marie Lette; Abou Abdallah Malick Diouara; Mathias Glaus (VertigO)
In light of public policy documents, sub-Saharan Africa, in general, and Senegal, in particular, seem to have resolutely committed to promoting the principles of the Circular Economy (CE). This contribution aims to document the current state of implementation and appropriation of practices and concepts in Senegal both by public authorities and by communities. The systemic analysis of the literature reveals an absence of a CE roadmap. However, significant reforms have been made to the regulations, particularly for the rational management of plastic waste and the extraction and exploitation of mineral resources. Other initiatives have also emerged with program variations focused on managing household waste and recovering organic waste, including electrical and electronic equipment. Awareness-raising efforts against wasting water and electricity have also received positive community responses. Under the impetus of government agencies and/or non-governmental organizations (NGOs), initiatives included in projects and programs through individual companies or even economic interest groups campaign for circular practices. In the agro-industry sector, the extension of hydro-agricultural developments has facilitated the emergence of business synergies among farmers, pastoralists, and agro-industries. Although public policies remain timid about appropriating the CE concept, several endogenous initiatives and practices at the community level are already similar.